2013
DOI: 10.1016/j.jacc.2012.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Fibrinogen Rather Than Residual Platelet Reactivity After Clopidogrel Pre-Treatment Is Associated With an Increased Ischemic Risk During Elective Percutaneous Coronary Intervention

Abstract: Elevated fibrinogen is independently associated with the risk of ischemic myocardial injury following elective PCI with clopidogrel pre-treatment regardless of platelet reactivity as measured by the VerifyNow assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Our concern is supported by the association observed between high fibrinogen levels and myocardial infarction [25] or stroke [11].…”
Section: Introductionmentioning
confidence: 63%
“…Our concern is supported by the association observed between high fibrinogen levels and myocardial infarction [25] or stroke [11].…”
Section: Introductionmentioning
confidence: 63%
“…This analysis revealed that at least 69 outcome events were needed 1. Collection of study data from eligible subjects was continued until 69 MACE events were recorded at 6 months, then enrollees had both 6‐month and 2‐year MACE events identified.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it has been identified as a risk factor for both short‐ and long‐term adverse cardiovascular events 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. More recently, elevated baseline fibrinogen level has been reported to be associated with higher on‐thienopyridine platelet reactivity, periprocedural myocardial infarction (MI), and combined MACE within 12 months of the index PCI 1, 2, 3, 15. The present study was performed to determine whether a longer term adverse relationship between baseline serum fibrinogen level, on‐thienopyridine platelet reactivity, and ischemic cardiovascular events exists in patients undergoing PCI for both elective or acute coronary syndrome (ACS) indications.…”
mentioning
confidence: 99%
“…Elevated fibrinogen levels have been prognostically associated with cardiovascular events after acute coronary syndrome and percutaneous coronary intervention. 11 The study by Kim et al extends those previous observation to offpump CABG, indicating that the prognostic benefit of being he package insert for clopidogrel recommends withholding the drug at least 5 days prior to any elective surgery, including coronary artery bypass grafting (CABG). Indeed, bleeding varied markedly compared with placebo in patients undergoing CABG in the Clopidogrel in Unstable Angina to Prevent Recurrent Events (CURE) trial according to whether clopidogrel was stopped for ≤5 days or >5 days before surgery.…”
mentioning
confidence: 82%